How is the Human Genome Project doing, and what have we learned so far? - Guyer, M S (1995)
In this paper, we describe the accomplishments of the initial phase of the Human Genome Project, with particular attention to the progress made toward achieving the defined goals for constructing genetic and physical maps of the human genome and determining the sequence of human DNA, identifying the complete set of human genes, and analyzing the need for adequate policies for using the information about human genetics in ways that maximize the benefits for individuals and society.